Digital communications : course and exercises with solutions - Jarry, Pierre, 1946- (London : ISTE Press, 2015)
Digital communications plays an important role in numerical transmission systems due to the proliferation of radio beams, satellite, optic fibbers, radar, and mobile wireless systems. This book provides the fundamentals and basic design techniques of digital communications with an emphasis on the systems of telecommunication and the principles of baseband transmission. With a focus on examples and exercises, this book will prepare you with a practical and real-life treatment of communication problems.
Chapter 3: Baseband Communications 3.1. Sampling the Signals ; 3.2. Coding the Samples ; 3.3. Time Multiplexing.
Online resource; title from PDF title page (EBSCO, viewed December 9, 2015).
Includes bibliographical references and index.
Keywords: Digital communications; TECHNOLOGY & ENGINEERING -- Mechanical; Digital communications; Electronic books